2009
DOI: 10.1093/rheumatology/kep295
|View full text |Cite
|
Sign up to set email alerts
|

A prospective open-label study of mycophenolate mofetil for the treatment of diffuse systemic sclerosis

Abstract: In this prospective open-label study of mycophenolate mofetil for the treatment of dcSSc, we observed significant improvements in skin scores, peripheral vascular involvement and patient-perceived health status. Pulmonary function studies did not worsen as expected, but instead showed a trend towards improvement. Controlled trials are needed to further investigate this trend for improved pulmonary function studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 16 publications
4
55
1
4
Order By: Relevance
“…The observed degree of improvement of mRSS in the study described here correlates well with prior studies by Derk et al (19) and Le et al (20) who found a reduction of 14.1 and 7.6 points in the mRSS of patients treated with MMF, respectively. Given the heterogeneous SSc course, the greater than 10 point mRSS improvement and the 23% reduction in affected BSA observed here are likely clinically significant for this population of previously untreated patients with SSc of 11 recent onset with diffuse cutaneous involvement and usually progressive clinical course.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The observed degree of improvement of mRSS in the study described here correlates well with prior studies by Derk et al (19) and Le et al (20) who found a reduction of 14.1 and 7.6 points in the mRSS of patients treated with MMF, respectively. Given the heterogeneous SSc course, the greater than 10 point mRSS improvement and the 23% reduction in affected BSA observed here are likely clinically significant for this population of previously untreated patients with SSc of 11 recent onset with diffuse cutaneous involvement and usually progressive clinical course.…”
Section: Discussionsupporting
confidence: 91%
“…Here, we describe a prospective observational study of MMF for the treatment of SSc in patients with recent onset of progressive diffuse cutaneous involvement. In contrast with other published studies (16)(17)(18)(19)(20) the patients included in our study had not received any previous immunosuppresive, immunomodulating, or antifibrotic therapy, and none of the patients received any other disease modifying therapy during the study.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Aunque en términos generales la evidencia está a favor de usarlo, en muchas ocasiones este medicamento se administró combinado con otros inmunosupresoras lo que impide establecer el beneficio aislado del micofenolato (34)(35)(36)(37)(38)(39)(40)(41)(42).…”
Section: ¿Cómo Tratar?unclassified
“…Although the toxicity of MMF appears tolerable, the longterm toxicity of MMF in this setting remains unknown. Whether MMF has additional disease-modifying benefits such as in improving the cutaneous involvement of SSc remains unclear 13,14,15,16 . Finally, as the authors note, it is unclear how long patients should be treated with MMF to avoid progression of lung fibrosis.…”
mentioning
confidence: 99%